Effects of Cooperative Learning on Students’ Academic Achievement - Fariha Gull; Shumaila Shehzad (Journal of Education and Learning (EduLearn), 2015)
Multiple teaching methods are used by teachers in order to improve learning of students. The most popular is lecture method, while very effective is cooperative learning method. Later teaching method had been preferred for teaching science and languages as cited by previous research studies. However, in the subjects of social sciences and humanities, its importance cannot be ignored. Following study is an effort to determine effect of cooperative learning method on students’ achievement in subject of Education.  Qusi experimental design, with pre and post test of control and experimental group was used to achieve target of the study. Sample of the study consisted of 63 female students enrolled in grade 12 of a public college. An achievement test was used as a pre-test, the students were than divided in experimental and control groups. Multiple cooperative learning activities were performed with experimental group by using three common methods of cooperative learning i.e., STAD, TGT and Jigsaw II. The control group was taught by lecture method only. After 8 weeks a post test was administered on both experimental and control group in order to identify difference in achievement. The independent sample t-test was used to measure the mean scores difference between achievement scores of control and treatment groups on pretest.  The results showed that there was no significant difference between the two groups (p=.825) leading to assumption that both groups were on equal level of achievement before intervention.  Same test was applied to find out difference between two groups before and after intervention.  The results showed that there was a significant difference in scores of control and experimental group in post-test. In addition to this paired sample t-test was conducted to compare the effect of intervention on achievement scores of experimental group.  The results showed that there was significant difference between scores of experimental group before and after intervention (p=.000). It can be concluded from results that cooperative learning activities had a positive effect on academic achievement of students enrolled in the subject of Education. This study is a contribution in knowledge body of teaching methods for social sciences. This had clarified that cooperative learning activities are equally helpful for the subject that was considered truly a lecture subject. The teachers can use this teaching method in their classes.